Effect of Intermittent Fasting on Improve Body Composition and Anthropometric Measurements of Women with Polycystic Ovarian Syndrome. - Abu Salma, Baha'a; Thekrallah, Fida; Qatawneh, Ayman; Hasan, Hanan; Shawaqfeh, Samar; Altarawneh, Mohammad (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Polycystic ovary syndrome is a metabolic disorder that affects women of reproductive age and is associated with insulin resistance. Objectives: The study aims to evaluate the effect of intermittent fasting and dietary intervention in improving anthropometric measures and body composition. Material and Methods: An interventional trial was carried out on eighty-six women between the ages of 19 and 40 with a body mass index of more than 25 kg/m2 were assigned to two intervention groups: the first group (n = 57) followed intermittent fasting plus dietary restriction, and the second group (n = 29) followed dietary restriction without intermittent fasting. Results: The results show that the fasting polycystic ovarian syndrome women experienced a significant (P < 0.05) increase in muscle mass (2.2 ± 2.4) compared to the non-fasting group (0.01 ± 1.5). At the end of the intervention, fasting women with the polycystic ovarian syndrome had significantly (P < 0.05) lost weight (9.2 ± 4.5kg), fat mass % (4.6 ± 3.4), and visceral fat (2.3 ± 2.1 kg), while gaining muscle mass (2.2 ± 2.4 kg). However, non-fasting women with polycystic ovarian syndrome showed significantly reduced body weight (2.4 ± 0.4 kg), fat mass % (1.2 ± 1.1), and visceral fat (0.5 ± 0.7). The results of the linear regression model showed that the highest effect of intermittent fasting was seen in weight, fat-free mass, and muscle mass. Body fat mass changed by 93% under the effect of intermittent fasting. Conclusion: Intermittent fasting may improve health outcomes, reduce body fat, maintain muscle mass, and aid weight loss in women with polycystic ovarian syndrome. Large-scale randomized controlled trials can improve our understanding of intermittent fasting in polycystic ovarian syndrome.